Biomass burning related ammonia emissions promoted a self-amplifying loop in the urban environment in Kunming (SW China). (15th May 2021) - Zhou, Yunhong; Zheng, Nengjian; Luo, Li; Zhao, Jingjing; Qu, Linglu; Guan, Hui; Xiao, Hongwei; Zhang, Zhongyi; Tian, Jing; Xiao, Huayun
Abstract: Particulate ammonium (NH4 + ) is one of the most important inorganic components in aerosol. The concentrations of NH4 + in PM2.5 significantly increased when PM2.5 levels elevated. Increased understanding of the atmospheric processes and sources of ambient ammonia is an effective way to control atmospheric ammonia and tackle air pollution problems. This study focused on the concentration and nitrogen stable isotopic composition of particulate NH4 + in PM2.5 in a southwest typical plateau city, Kunming. The trend in NH4 + concentrations was parallel to the trend in PM2.5 levels, with obviously increased concentrations observed in November. Aerosol pH and liquid water content (ALWC) were synchronously simulated by the ISORROPIA-II model. And the ammonia gas-particle conversion ratio ( f ) was calculated for each day. Then, we proposed that a self-amplifying feedback mechanism of NH4 + formation was associated with the variations of ALWC, pH, and the ammonia gas-particle conversion ratio. Based on the inverse analysis of the nitrogen isotopic composition of particulate NH4 +, the corresponding δ 15 N values of initial ambient NH3 were estimated to be −27.4‰–15.3‰, with an average of −8.1 ± 8.3‰. Results from Back trajectory analysis, PSCF analysis, and isotope-based source apportionment of NH3 shed light on source compositions and potential source regions, indicating that, in the study area, ambient NH3 during slightly polluted days were dominated by biomass burning emissions, which might have been originated from local emissions and regional transport process in late autumn. Graphical abstract: Image 1 Highlights: A self-amplifying loop was proposed when the concentration of NH4 + in PM2.5 elevated in late autumn in Kunming. Biomass burning related ammonia emissions significantly enhanced during slightly polluted days. Increased biomass burning emissions in Kunming were related to ammonia emissions from local area and regional transport.